Evaluation of Teaching Curriculum of Anaesthesiology by the Undergraduate Medical Students - Alam, MR; Islam, MZ (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Students' feedback is a recommended tool to evaluate the merit of a teaching curriculum. Search of literature, however, reveals a very few such attempts on the subject of anaesthesiology in medical undergraduate level. Objective: The reported study was conducted to evaluate the undergraduate course curriculum of medical students from students' feedback. Method: To judge the students' viewpoint, a pertinent and simple questionnaire was designed to collect the feedback from the final year MBBS students of AFMC Dhaka for five consecutive years. Students were asked to fill up the questionnaire on completion of their placement. Result: A total of 253 students had participated in this unbiased and anonymous feedback. While 96.7% students agreed that the posting provided them an insight into the subject of anaesthesiology and critical care but 38.3% found that the duration of posting was inadequate. Though 98.8% students responded that the topics were interesting but only 56.8% found that the practical demonstrations were adequate. The three top ranking topics of interest in decreasing order were cardiopulmonary resuscitation (93.6%), airway maintenance along with endotracheal intubation (55.2%) and spinal anaesthesia (32.5%). Interestingly these three topics were demonstrated practically along with theory sessions. Not surprisingly the three commonest suggestions were prolonging the duration (34.8%) as well as practical demonstrations (31.2%) and more opportunity to 'hands on practice' (24.5%). Conclusion: This little effort may help the curriculam reviewers to think. Key words: Curriculum of anaesthesiology; undergraduate; students feedback DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8618 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 8-10